(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The paper is to present about identification of electronic junk mail called spam by LSTM layers in recurrent neural network. These methods are applied for detecting and filtrating of those junk messages in successful manner. This is to give high accuracy frequency as because it is used to simplify the text into word format. The most important factor in purchasing a product that customer looks for reviews in online, even producers and dealers are monitored on those reviews from customers because of the created collection. Development of a technique is important to detect and also to filter spam as for the profit spammers usually manipulate the reviews. In this, Artificial Intelligence model is proposed effectively to continuous recognition of those mail shot.